Structural Analysis of Social Behavior: Using Cluster Analysis to Examine Intrapsychic Personality Traits Associated With Depression in Women With Breast Cancer. (14th May 2022) - Vespa, Anna; Giulietti, Maria Velia; Fabbietti, Paolo; Di Rosa, Mirko; Gattafoni, Pisana; Sarzani, Riccardo; Arnaldi, Giorgio; Balercia, Giancarlo; Berardi, Rossana; Salvo, Gianmaria; Attademo, Luigi; Spatuzzi, Roberta
Background: This study aimed to investigate personality traits associated with depression in breast cancer women (BCW). Methods: Sample: 236 BCW recently diagnosed (early stages). Tests: SASB-Structural-Analysis of Social-Behavior; IPAT-CDQ-Depression . Statistical analysis: cluster K-Means analysis to explore SASB personality-traits considering the 8 SASB clusters (Cl); CDQ scores dichotomized by 50th percentile cutoff (high/low); Pearson's chi square test to compare CDQ levels and SASB traits. Results: Cluster analysis results supported two distinguishable SASB personality traits (for all SASB Cl-Scales P < .001) classified as "Love and Autonomy" (62.2%) and "Control and Hate" (37.8%). Patients with Love/Autonomy traits are spontaneous, accept their deepest feelings and desire to be close to other people (Cl1, Cl2, Cl3, Cl4). They show a medium value of self-control and a low tendency to self-abusive and self-critical behaviors (Cl5, Cl6). They pay attention to themselves and to their needs at emotional and physical levels also if may be occasionally engaged in self-destructive behaviors (Cl7, Cl8). Women with Control/Hate traits are not spontaneous and do not always express emotions (C1, Cl2, Cl3, Cl4) and flexibility in their relationship with others (Cl5, Cl6). In stressful situations, they may ignore the option of choices for self-growth and neglect their needs and those of others (Cl7, Cl8). BCWs with Control/Hate traits scored higher in depression ( P <.001) than those with the Love/Autonomy profile. Conclusions: Healthcare professionals should be aware of these personality traits and their association with depression to identify the psychologically most vulnerable BCW and improve the care they provide them. The psychotherapeutic intervention should be planned to face on the personality problems.